Capacity-building of Ward Committee members for community engagement in Johannesburg’s Ward 68 - Hlungwana, Jabulani (University of the Witwatersrand, Johannesburg, 2024)
The dawn of democracy in South Africa brought a glimmer of hope to the people by assuring them that they would be part of the decision-making process of development that affected them. The cornerstone for this is public participation, which remains the driving principle of engaging communities when making development decisions. In the centre of this, municipalities use Ward Committees to facilitate and organise people to take part in the different platforms made available for community engagement and participation. Ward Committees represent the needs and aspirations of the residents and for them to function well, there is a need for effective community engagement. This study investigated the capacity-building initiatives amongst ward committees in Ward 68, which is situated within the City of Johannesburg. The focus of the investigation was to establish ways of enhancing the skills and knowledge that Ward Committee members needed to build positive relationships with the communities. The literature depicted capacity-building as a crucial component of empowering employees to discharge their duties. It presented the different types of capacity- building levels that shape frameworks that can be adopted and tailored to the Ward Committees of Ward 68. The study described the challenges confronted by ward committees while attempting to fulfil their roles and responsibilities of galvanising residents to participate and engage in issues that pertain to the development of their community. The study also detailed the context of ward committees as catalysts for community engagement. A qualitative method was used to answer the research questions. The researcher collected data through semi-structured interviews. The researcher collected primary data by interviewing ten members of the Ward Committee, who gave in-depth views about their experiences. Secondary data were collected through analysing published journals, government reports, and the City of Johannesburg reports. The study recorded key findings about the themes and patterns that were identified during the process of thematic analysis in a quest to answer the research questions. The themes that came out of the process stemmed from the roles and responsibilities of ward committees and the challenges that they faced. The other three themes that emerged related to the kinds of capacity-building offered by the City of Johannesburg, the effectiveness of the training in creating trust with communities and municipal officials, and the low levels of education within the community, which negatively impacted the residents’ understanding of how governance operated. The key findings of the study were as follows: the CoJ only conducted induction training for the Ward Committees, some Ward Committees could not attend the induction training due to different reasons; others attended, but they could not recall the content of the training; and several other challenges hindered the effectiveness of Ward Committees.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Capacity Building; Public participation; Ward Committees; SDG-11: Sustainable cities and communities